Insights from the comparisons of SARS-CoV and COVID-19 outbreaks: The evidence-based experience of epidemic prevention in China. Issue 6 (12th February 2021) - Liu, Wen-Yi; Chuang, Yen-Ching; Liu, Ting-Jun; Chien, Ching-Wen; Tung, Tao-Hsin
Abstract : Abstract: Coronavirus disease 2019 (COVID-19) is one of infectious diseases caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). At the beginning of 2020, a sudden outbreak of novel pneumonia, originated from Wuhan, China, swiftly evolves to a worldwide pandemic, alike the severe acute respiratory syndrome (SARS) in 2003. However, Chinese-style innovation in response to the outbreak of COVID-19 helped China to reach a faster and more effective success in the containment of this epidemic. This review summarizes insights from the comparisons of severe acute respiratory syndrome coronavirus (SARS-CoV) and COVID-19 outbreaks on the basis of preventive strategies in China for this coronavirus pandemic.